1994
DOI: 10.1017/s0022112094002326
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-driven flow of suspensions: simulation and theory

Abstract: Dynamic simulations of the pressure-driven flow in a channel of a non-Brownian suspension at zero Reynolds number were conducted using Stokesian Dynamics. The simulations are for a monolayer of identical particles as a function of the dimensionless channel width and the bulk particle concentration. Starting from a homogeneous dispersion, the particles gradually migrate towards the centre of the channel, resulting in an homogeneous concentration profile and a blunting of the particle velocity profile. The time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
617
4
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 660 publications
(642 citation statements)
references
References 17 publications
19
617
4
2
Order By: Relevance
“…On the other hand, normal stresses are crucial since they determine the migration of particles in suspensions subjected to an inhomogeneous shear field (Nott & Brady 1994;Mills & Snabre 1995;Morris & Boulay 1999;Nott et al 2011;Lhuillier 2009). This paper therefore intends to address this issue by considering numerical simulations of suspensions accounting for friction and roughness.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, normal stresses are crucial since they determine the migration of particles in suspensions subjected to an inhomogeneous shear field (Nott & Brady 1994;Mills & Snabre 1995;Morris & Boulay 1999;Nott et al 2011;Lhuillier 2009). This paper therefore intends to address this issue by considering numerical simulations of suspensions accounting for friction and roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Of the proposed theories, the most frequently used and quoted in the literature are the diffusive flux model proposed by Leighton and Acrivos, 1 and the suspension balance model proposed by Nott and Brady. 2 Both models supplement the equations of motion for the suspension with equations that describe the motion of the particles. The diffusive flux model is purely kinematic, in the sense that the flux of the particles in the suspension is described in terms of the gradients of the particle concentration and the strain rate.…”
Section: Introductionmentioning
confidence: 99%
“…The suspension balance model attempts to relate the rheology of the suspension with the migration flux of the particles. Nott and Brady 2 showed that the diffusive flux model can be recovered from the suspension balance model, thereby showing that the two models share the same physical origin. This paper addresses the suspension balance model ͑hereafter referred to as the SBM͒, but insofar as the two models are connected, its conclusions do have a bearing on the diffusive flux model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear-induced migration occurs in a wide variety of flows other than viscometric ones, including the well-studied case of pressure-driven flows. These shearinduced migrations are argued to result from normal stress imbalances according to macroscopic, multiphase models (Nott & Brady 1994). Indeed, concentrated suspensions of spheres have measurable normal stress differences, a notable non-Newtonian characteristic (Hinch 2011).…”
Section: Introductionmentioning
confidence: 99%